Basic density and moisture content of coniferous branches and wood in Northern Norway - Vadla K.; Dibdiakova J. (EPJ Web of Conferences, 2012)
With the increasing demand for fuel the use of biomass from other tree components like branches and tops has increased rapidly. Norway has abundant raw material resources which can be use for bioenergy. Sitka spruce and Norway spruce are becoming more interesting due to their potential energy for heating. The study consisted of 2 site locations in Nordland – 1 stand of Sitka spruce in Steigen area, and 1 stand of Sitka spruce, 1 stand of Norway spruce, and 1 stand of Lutz spruce in Sømna area. Bark thickness differed between the sites within decreasing pattern along the stem. Significant differences of bark density between sites, tree species and tree height levels with decreasing trend towards the top were found. Branches density decreased along the crown level and had about 15-20% higher density than wood density. Wood density varied significantly with sites and height of tree – highest pattern on the tree base, decreasing to 20% of height, and again increasing to the top. The moisture content of branches, wood and bark increased from the base of tree to the top. Bark moisture was about 20-25% higher as wood moisture content. Sitka spruce in Northland may be highly considered as a valuable bioenergy source.